2002
DOI: 10.1111/j.1745-6584.2002.tb02547.x
|View full text |Cite
|
Sign up to set email alerts
|

A Global Experimental System Approach of Karst Springs1 Hydrographs and Chemographs

Abstract: Investigation techniques for karst flow systems are based mainly on the study of different signals leaving the system caused by natural or induced external influences. Each signal represents one of the systems outputs (e.g., hydraulic, chemical, physical, or isotopic responses) that reflect the characteristics of the entire system. In this paper, we present a method to infer information about the structure of karst systems. It is based on a simultaneous analysis of chemical and hydraulic responses. Beside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…In remote mountain areas this could lead to water shortages, as replacement water would have to be transported from far away to regions lacking glacial meltwater. Recent research has been focusing on assessing water resources from karstic environment using karst models (Doerfliger et al, 1999;Butscher and Huggenberger, 2009;Jeannin et al, 2013), artificial tracer experiments (Goldscheider et al, 2008) and chemical and isotopic composition in runoff water (Grasso and Jeannin, 2002). Nevertheless, to assess current and future water resources, it is necessary to combine the three techniques and assemble the results in an illustrative karst model.…”
Section: Introductionmentioning
confidence: 99%
“…In remote mountain areas this could lead to water shortages, as replacement water would have to be transported from far away to regions lacking glacial meltwater. Recent research has been focusing on assessing water resources from karstic environment using karst models (Doerfliger et al, 1999;Butscher and Huggenberger, 2009;Jeannin et al, 2013), artificial tracer experiments (Goldscheider et al, 2008) and chemical and isotopic composition in runoff water (Grasso and Jeannin, 2002). Nevertheless, to assess current and future water resources, it is necessary to combine the three techniques and assemble the results in an illustrative karst model.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the response of karstic aquifers to storms is one of the main techniques that has been applied. The bulk of the previous work on storm pulses in karstic aquifers can be grouped into those studies that analyze rainfall-spring discharge relations [e.g., Ashton, 1966;Brown, 1970;Knisel, 1972;Brown, 1973;Dreiss, 1982;Labat et al, 2000aLabat et al, , 2000bDenic-Jukic and Jukic, 2003;Panagopoulos and Lambrakis, 2006] and those studies that attempt to ascertain the properties of the aquifer through characterization of the hydrographs, sometimes complemented by chemographs or thermographs [e.g., Dreiss, 1983;Eisenlohr et al, 1997;Kiraly et al, 1995;Grasso and Jeannin, 2002;Grasso et al, 2003;Birk et al, 2004;Kovács et al, 2005;Birk et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…However, Eisenlohr et al [1997] suggested that the shape of spring hydrographs are a function of the structure of the aquifer, the form of the floods, the frequency of storm events, and the type of infiltration. Grasso and Jeannin [2002] interpret hydrographs and chemographs in terms of both aquifer structure and bioclimatic variables. The previously cited group of studies that focused on rainfall-discharge relations used rainfall as the input signal even in cases where the actual input signal is a losing stream or lake.…”
Section: Introductionmentioning
confidence: 99%
“…Teutsch and Sauter, 1991). Spring hydrograph, chemograph, and tracer breakthrough curve analysis focus on small-scale effects of karst conduits to define the size and the characteristics of one individual spring aquifer (Birk et al, 2004;Einsiedl, 2005;Geyer et al, 2008;Bonacci, 2004;Hauns et al, 2001;Kovacs et al, 2001;Grasso and Jeannin, 2002;Maloszweski et al, 2005;Weiler et al, 2003). Other approaches concentrate on karst genesis or theoretical conduit flow (Sauter et al, 2006;Romanov et al, 2004;Ford, 2003).…”
Section: G Kraller Et Al: Water Balance Estimation In High Alpine Tmentioning
confidence: 99%